2001
DOI: 10.1093/humrep/16.6.1264
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twinning after assisted reproductive techniques: a phenomenon independent of micromanipulation

Abstract: A 3 year retrospective analysis was conducted of pregnancies achieved after various assisted reproductive treatment modalities in our infertility practice, to calculate and compare the rates of monozygotic twinning (MZT). A total of 731 pregnancies achieved after various assisted reproduction treatments were reviewed. Gonadotrophin therapy for induction of ovulation and controlled ovarian hyperstimulation (COH) yielded 129 clinical pregnancies. Conventional IVF yielded 139 pregnancies. IVF and intracytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(139 citation statements)
references
References 19 publications
3
131
2
3
Order By: Relevance
“…We speculate that this abnormal development was neither laboratory specific nor patient specific. Schieve et al [7], Schachter et al [8], and Milki et al [9] identified assisted hatching, extended culture, and vitrification followed by warming as possible reasons for monozygotic twinning. However, as we followed our standard procedure in this case, the mechanism behind this abnormal development is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this abnormal development was neither laboratory specific nor patient specific. Schieve et al [7], Schachter et al [8], and Milki et al [9] identified assisted hatching, extended culture, and vitrification followed by warming as possible reasons for monozygotic twinning. However, as we followed our standard procedure in this case, the mechanism behind this abnormal development is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of monozygotic twinning has been reported in pregnancies conceived after ovarian induction, IVF/ICSI procedure, especially in blastocyst transfer(s) [19][20][21][22][23]. We projected multiple pregnancy rates from the results of blastocyst stage transfers in our clinic from this study that included 3 cases of monozygotic twinning in 126 pregnancies (2.38%).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the rates of monozygotic twinning were higher in the group with neither AH or ICSI but the differences were not statistically significant (P = 0.4). Schacter et al [5] reviewed 731 pregnancies achieved after assisted reproductive procedures over the 3 year period from 1997-1999. Including pregnancies from COH, IVF, and ICSI procedures they found an overall rate of monozygotic twinning rate of 0.95% (7/731).…”
Section: Discussionmentioning
confidence: 99%